MANAGEMENT PROBLEMS OF ALMAJIRI MODEL SCHOOLS FOR THE ATTAINMENT OF THE OBJECTIVES OF PRIMARY EDUCATION IN NIGERIA: A CASE STUDY OF NORTH-WEST GEO-POLITICAL ZONE - Omotayo, D. M.; Sulaiman, H. A. (Sokoto Educational Review, 2013)
This study empirically investigated the envisaged management problems of the Almajiri Model schools education programme. Specifically, it investigated how inadequate public awareness, funding, the dearth of specially trained teachers, inadequate provision of educational facilities and supervisions hinder the effective implementation of the programme for the attainment of the objectives. A ten-item self-designed questionnaire was administered on 1,132 respondents sampled out of the total population of four groups of teachers, officials, community’ and religious leaders of 30,540 stakeholders in the area of study. The respondents indicated their position on three rating scales of Agree, Undecided and Disagree. Descriptive statistics and chi-square statistical analyses were employed to test the null hypothesis at the 0.05 level of significance. The null hypothesis of the study was accepted in view of the fact that the result showed no significant difference in the calculated value. The findings of the study showed that all the envisaged management problems are prevalent and should be properly tackled in order to achieve the objectives of Primary Education and Almajiri Model Programme in Nigeria. Based on the findings it was recommended among other things that public awareness, especially at the grass-root level, is necessary to educate parents and community members on the importance of Almajiri Model Schools.